2013
DOI: 10.1603/me12065
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and Memory of Sand Flies in an Endemic Area of Cutaneous Leishmaniasis, Southern Brazil

Abstract: The dispersal of and the existence of memory in sand flies were measured in a transmission area of cutaneous leishmaniasis, in the municipality of Bandeirantes, Paraná, Brazil. Sand flies were caught in a rural area, with Shannon trap installed in the forest and three Falcão traps installed in a human-inhabited environment (HIE) and three others in an impacted environment presently uninhabited by humans (EUH), from 1800 to 0600 hours. The captured sand flies were marked with yellow, blue, or red fluorescent po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Using mark-recapture methods, Guerra-Silva et al [36] showed that sand flies, the vectors of the American cutaneous leishmaniasis, were able to return to their initial location after being released in an unknown area. The use of learned spatial, visual or olfactory cues by sandflies could be just one of the possible explanations for this behavior, but further work is still needed to assess whether or not sand flies rely on learned information.…”
Section: Recent Advances In Vector Learning and Memorymentioning
confidence: 99%
“…Using mark-recapture methods, Guerra-Silva et al [36] showed that sand flies, the vectors of the American cutaneous leishmaniasis, were able to return to their initial location after being released in an unknown area. The use of learned spatial, visual or olfactory cues by sandflies could be just one of the possible explanations for this behavior, but further work is still needed to assess whether or not sand flies rely on learned information.…”
Section: Recent Advances In Vector Learning and Memorymentioning
confidence: 99%
“…Recent advances in disease vector pest management have highlighted the importance of understanding the effects of experience on insect behavior [23,24,25]. Human disease vectors, such as mosquitoes [26,27,28,29,30], kissing bugs [31,32], tsetse flies [33,34], and sandflies [35], demonstrate ecologically significant learning events, driving host selection and oviposition site preferences via visual, olfactory, and even thermal stimulus experiences [23]. Similarly, D. citri behaviors, ranging from host preference to mate choice, may be guided by experience-dependent visual and olfactory associations with the host environment and conspecifics [36].…”
Section: Introductionmentioning
confidence: 99%
“…There are many different possible explanations for the marked differences observed in the distance that the males and females would travel and the recapture rates at the two sites. Attraction and capture of an insect is a complex process involving multiple components, several critical elements may individually or collectively be important; i) spatial memory/olfactory memory: one possibility is that sand flies were capable of learning a familiar area map to facilitate movement and specific routes between feeding, resting and breeding sites [ 53 56 ], ii) population density: a natural aggregation in the chicken shed producing large quantities of pheromone would compete with the synthetic pheromone, causing a reduction in the number of specimens attracted to pheromone-baited traps [ 53 , 57 ], iii) fidelity to specific hosts might influence the recruitment of sand flies in locations in which there is an availability of sources of blood [ 53 , 55 , 58 ], and iv) abiotic factors could explain the dispersal of Lu . longipalpis at the two sites, in particular high wind speed has been attributed to decreasing or failing collections as it interferes with sand fly flight [ 59 61 ].…”
Section: Discussionmentioning
confidence: 99%